2016
DOI: 10.1144/sp438.9
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of crustal heterogeneity and lithospheric processes in determining passive margin architecture on the southern Namibian margin

Abstract: Abstract:The influence of pre-rift crustal heterogeneity and structure upon the evolution of a continental rift and its subsequent passive margin is explored. The absence of thick Aptian salts in the Namibian South Atlantic allows imaging of sufficient resolution to distinguish different pre-rift basement seismic facies. Aspects of pre-rift basement geometry have been characterized which are then compared with the geometries of Cretaceous rift basin structure, and of subsequent post-rift margin architectural e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 68 publications
1
13
0
Order By: Relevance
“…Furthermore, the 9 SDR packages in our profile represent a total width of 80 km and, although we cannot quantify the duration of the individual volcanic events, biostratigraphic constraints from equivalent SDRs on the Namibian margin constrain the age of the entire SDR system to be between the latest Valanginian-Hauterivian (ca. 133 Ma) and magnetic chron M4 (126 Ma; Wickens and Mclachlan, 1990;Cohen et al, 2014;Mohammed et al, 2016). This gives an oceanic halfspreading rate of 11 mm/yr, which conforms to predicted rates of early South Atlantic opening (Heine and Brune, 2014).…”
Section: Implications and Conclusionsupporting
confidence: 55%
“…Furthermore, the 9 SDR packages in our profile represent a total width of 80 km and, although we cannot quantify the duration of the individual volcanic events, biostratigraphic constraints from equivalent SDRs on the Namibian margin constrain the age of the entire SDR system to be between the latest Valanginian-Hauterivian (ca. 133 Ma) and magnetic chron M4 (126 Ma; Wickens and Mclachlan, 1990;Cohen et al, 2014;Mohammed et al, 2016). This gives an oceanic halfspreading rate of 11 mm/yr, which conforms to predicted rates of early South Atlantic opening (Heine and Brune, 2014).…”
Section: Implications and Conclusionsupporting
confidence: 55%
“…[] illustrated this for the southern margin of the western Corinth Rift with migration between north dipping faults (i.e., Kalavryta Fault to the Eliki Fault; Figures a–c). Similar observations are seen at a number of margins including Iberia and Namibia [ Ranero and Pérez‐Gussinyé , ; Mohammed et al ., ]. For example, at the Iberian margin brittle deformation is accommodated by sequentially active faults that young and dip oceanward [e.g., Wilson et al ., ; Ranero and Pérez‐Gussinyé , ].…”
Section: Discussionmentioning
confidence: 99%
“…The development of asymmetry in a rift zone is relatively common, for example, in much of the East African rift zone [Ebinger and Scholz, 2012]. Many studies have documented spatial variability in fault polarity and rift symmetry within rifts, including the Gulf of Suez [Patton et al, 1994;Bosworth et al, 2005], East Africa [Rosendahl, 1987;Hayward and Ebinger, 1996], the now inactive North Sea [Cowie et al, 2000], and fully evolved passive margin settings [Mohammed et al, 2016]. Models indicate that rift development should be spatially and temporally variable due to variations in fault timing and activity, with rifts developing from numerous isolated basins to a single laterally continuous half graben [e.g., Cowie et al, 2000].…”
Section: Rapid Changes In Fault Polarity and Rift Symmetrymentioning
confidence: 99%
“…We choose a DWFTB within the Orange Basin (Figure 9), offshore South Africa and Namibia, because the geological evolution of the margin has been well established (Gerrard & Smith, 1982, Brown et al, 1995, Mohammed et al, 2015 and DWFTBs are a well-documented and common feature found throughout the basin (Muntingh & Brown, 1993, Paton et al, 2008, Peel et al, 2014, Dalton et al, 2016. Restorations of these DWFTBs have been undertaken by de Vera et al (2010), and Dalton et al…”
Section: Application To Seismic Scale; Orange Basinmentioning
confidence: 99%